Applied intermediate macroeconomics - Hoover, Kevin D., 1955- (Cambridge ; New York : Cambridge University Press, 2012)
"This textbook offers a complete course in applied macroeconomics at the intermediate level that emphasizes the application of economic the ory to real-world data and policy"--Provided by publisher.
"This book is a complete course in applied macroeconomics that empha sizes the application of economic theory to real-world data and policy. Topics covered include national income, international, and financial a ccount, labor markets, aggregate supply and demand, inflation, and mone tary and fiscal policy. It is unique in developing a detailed toolkit o f elementary statistics and graphical techniques for economic data. A s trength is its detailed treatment of financial markets (national and in ternational), and the institutions of monetary and fiscal policy, which makes it especially helpful in understanding recent economic crises"-- Provided by publisher.
Machine generated contents note: Part I. Introduction: 1. Macroecono mics and the real world; Part II. The National Accounts: 2. The nationa l accounts and the structure of the economy; 3. Understanding gross dom estic product; 4. Measuring prices and inflation; Part III. Trends and Cycles: 5. Trends and cycles; Part IV. Financial Markets: 6. The financ ial system; 7. The behavior of interest rates; 8. The international fin ancial system and the balance of payments; Part V. Aggregate Supply: 9. Aggregate production; 10. Economic growth; 11. The ideal labor market; 12. Unemployment and the labor market process; Part VI. Aggregate Dema nd: 13. An introduction to aggregate demand; 14. Consumption and invest ment: a deeper look; Part VII. Macroeconomic Dynamics: 15. The dynamics of output, unemployment, and inflation; Part VIII. Macroeconomic Polic y: 16. Monetary policy; 17. Fiscal policy; Part IX. Macroeconomic Data: A Guide to Working with Economic Data.
Includes bibliographical references and index.
Keywords: Macroeconomics